2018
DOI: 10.1002/chem.201705927
|View full text |Cite
|
Sign up to set email alerts
|

Features of Auxiliaries That Enable Native Chemical Ligation beyond Glycine and Cleavage via Radical Fragmentation

Abstract: Native chemical ligation (NCL) is an invaluable tool in the total chemical synthesis of proteins. Ligation auxiliaries overcome the requirement for cysteine. However, the reported auxiliaries remained limited to glycine-containing ligation sites and the acidic conditions applied for cleavage of the typically applied N-benzyl-type linkages promote side reactions. With the aim to improve upon both ligation and cleavage, we systematically investigated alternative ligation scaffolds that challenge the N-benzyl dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 65 publications
1
24
0
3
Order By: Relevance
“…Canne et al (1996) introduced another way of circumventing the cysteine moiety by auxiliarated NCL introduced with the N α -(ethanethiol) and N α -(oxyethanethiol)-peptide. In Loibl et al (2018) applied this protocol for cleavage of 2-mercaptoethyl auxiliary group. A recently introduced NCL approach, the diselenide-selenoester ligation (DSL) opens up possibilities for using further amino acids and will be elucidated in the outlook.…”
Section: Follow-up Protocolsmentioning
confidence: 99%
“…Canne et al (1996) introduced another way of circumventing the cysteine moiety by auxiliarated NCL introduced with the N α -(ethanethiol) and N α -(oxyethanethiol)-peptide. In Loibl et al (2018) applied this protocol for cleavage of 2-mercaptoethyl auxiliary group. A recently introduced NCL approach, the diselenide-selenoester ligation (DSL) opens up possibilities for using further amino acids and will be elucidated in the outlook.…”
Section: Follow-up Protocolsmentioning
confidence: 99%
“…Die Verlagerung des Phenylsubstituenten von der α‐ zur β‐Position verringert den sterischen Anspruch in der Nähe des reaktiven Amins, wodurch das MPE‐Auxiliar auch NCL‐Reaktionen an nicht‐glycinhaltigen Verbindungen wie Ala‐Asn, Leu‐Asn erlaubt und die Ligation mit sterisch anspruchsvolleren Aminosäureresten wie Arg, Met und Gln ermöglicht. Nach der Ligation wird das MPE‐Auxiliar durch eine radikalische Fragmentierungsreaktion entfernt [8b] . Jedoch sind sterisch stark gehinderte Verknüpfungen an β‐verzweigten Aminosäuren auch mit diesem Auxiliar nicht zugänglich.…”
Section: Einführungunclassified
“…A suitable ligation template should provide high reactivity for both the thiol exchange and the S → N acyl migratory steps and must lend itself to facile removal under conditions that leave the ligation product unharmed. We systematically analyzed the architecture of the ligation template and found that the substituents at the α‐ and β‐positions in 15′ play key roles . A comparison of the three mercaptoethyl templates ME, MP, and MPE showed, perhaps surprisingly, that the additional β‐substituents in MP and MPE accelerated the ligation.…”
Section: Unimolecular Templates As Ligation Scaffolds In Protein Syntmentioning
confidence: 99%
“…However, we discovered a potentially general approach for the removal of N‐amide–linked mercaptoethyl groups. Nuclear magnetic resonance (NMR) analysis of a C 13 ‐labelled ligation template suggested that treatment with phosphine in aqueous morpholine at pH 8.5 triggers a radical‐induced oxidative fragmentation (Figure B) . The investigation led us to the 2‐mercapto‐2‐phenethyl (MPE) template, which is the first ligation auxiliary that enables NCL at ligation sites beyond glycine.…”
Section: Unimolecular Templates As Ligation Scaffolds In Protein Syntmentioning
confidence: 99%
See 1 more Smart Citation